Penerapan Self Management Conselling dengan Tipe Small Group Discussion dalam Membentuk Kecerdasan Emosional Peserta Didik Kelas XI IPS 1 di SMAN Umbulsari Kabupaten Jember - Rosyadi, Imron (Lembaga Yasin AlSys, 2024)
This research aims to explore the application of Self Management Counseling through Small Group Discussion in shaping the emotional intelligence of grade XI IPS 1 students at SMAN Umbulsari, Jember Regency, in the academic year 2022-2023. A qualitative method with a descriptive approach was employed to collect data through observation, interviews, and documentation. The study involved 31 students as research subjects. The results indicate that through the implementation of this model, students can develop skills in problem formulation, questioning and answering, as well as balancing emotional and logical intelligence. Furthermore, the implementation of this model also fosters collaboration within groups. These findings contribute to a better understanding of the importance of learning strategies that integrate self-management skills with small group discussions in shaping students' emotional intelligence.